Dyspnoea in patients receiving noninvasive ventilation for acute respiratory failure: prevalence, risk factors and prognostic impact: A prospective observational study. Issue 2 (9th August 2018) - Dangers, Laurence; Montlahuc, Claire; Kouatchet, Achille; Jaber, Samir; Meziani, Ferhat; Perbet, Sébastien; Similowski, Thomas; Resche-Rigon, Matthieu; Azoulay, Elie; Demoule, Alexandre
Dyspnoea is a frequent and intense symptom in intubated patients, but little attention has been paid to dyspnoea during noninvasive mechanical ventilation in the intensive care unit (ICU). The objectives of this study were to quantify the prevalence, intensity and prognostic impact of dyspnoea in patients receiving noninvasive ventilation (NIV) for acute respiratory failure (ARF) based on secondary analysis of a prospective observational cohort study in patients who received ventilatory support for ARF in 54 ICUs in France and Belgium. Dyspnoea was measured by a modified Borg scale. Among the 426 patients included, the median (interquartile range) dyspnoea score was 4 (3–5) on admission and 3 (2–4) after the first NIV session (p=0.001). Dyspnoea intensity ≥4 after the first NIV session was associated with the Sequential Organ Failure Assessment Score (odds ratio (OR) 1.12, p=0.001), respiratory rate (OR 1.03, p=0.032), anxiety (OR 1.92, p=0.006), leaks (OR 2.5, p=0.002) and arterial carbon dioxide tension (OR 0.98, p=0.025). Dyspnoea intensity ≥4 was independently associated with NIV failure (OR 2.41, p=0.001) and mortality (OR 2.11, p=0.009), but not with higher post-ICU burden and altered quality of life. Dyspnoea is frequent and intense in patients receiving NIV for ARF and is associated with a higher risk of NIV failure and poorer outcome. Dyspnoea is frequent in patients who receive NIV in the ICU and is associated with a poorer outcome http://ow.ly/sh3Z30kaieo